2011
DOI: 10.1007/s11011-011-9236-z
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral immune challenge with dsRNA enhances kainic acid-induced status epilepticus

Abstract: Clinical evidence implicates peripheral inflammatory diseases as comorbid factors in epilepsy. The present study was designed to determine the effect of the acute phase of antiviral response on seizure susceptibility. Young adult mice were intraperitoneally injected with 12 mg/kg of a viral mimic, polyinosinic:polycytidylic acid (PIC). After 48 h, seizures were induced by subcutaneous injection of kainic acid (KA). PIC-pretreatment profoundly enhances vulnerability to excitotoxic insult as evidenced by increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 13 publications
3
20
0
Order By: Relevance
“…The present study extends our previous finding that peripheral APR induced by a viral mimic, PIC, increases the susceptibility to KA-induced excitotoxicity (Kirschman et al 2011). Here, we have demonstrated that the window of increased susceptibility lasts up to 3 days after PIC challenge (Fig.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The present study extends our previous finding that peripheral APR induced by a viral mimic, PIC, increases the susceptibility to KA-induced excitotoxicity (Kirschman et al 2011). Here, we have demonstrated that the window of increased susceptibility lasts up to 3 days after PIC challenge (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…We have previously demonstrated that PIC challenge strongly enhances the susceptibility of mice to KA-induced seizures (Kirschman et al 2011). However, this feature was analyzed only 48 h after PIC injection.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, we used a combination of pIC and PILO to induce iSE in our mouse model. The doses of pIC and PILO were decided by past studies [13][14][15][16]. Midazolam was then administered 1 h after PILO-induced seizure.…”
Section: Introductionmentioning
confidence: 99%